Modern Philosophy: An introduction and survey - Scruton, Roger (London Sinclair-Stevenson, 1994)
Philosopher Roger Scruton offers a wide-ranging perspective on philosophy, from logic to aesthetics, written in a lively and engaging way that is sure to stimulate debate. Rather than producing a survey of an academic discipline, Scruton reclaims philosophy for worldly concerns